2011
DOI: 10.1016/j.vaccine.2011.05.088
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of immune response to an antigen delivered by vaccinia virus by displaying the antigen on the surface of intracellular mature virion

Abstract: Vaccinia virus (VACV) is the vaccine for smallpox and a widely-used vaccine vector for infectious diseases and cancers. The majority of the antibodies elicited by live VACV vaccination respond to virion structural proteins, including many integral membrane proteins on the intracellular mature virion (MV). Here, we showed that antibody response to an exogenous antigen delivered by VACV was greatly enhanced by incorporating the antigen as an integral membrane protein of MV. We constructed recombinant VACV expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…Intriguingly though, the study with recombinant vaccinia also assessed the merits of membrane-binding versus secretion of the encoded P. falciparum MSP1 antigen and reported the highest levels of functional antibody induction when the antigen was designed to anchor in the membrane. Similar observations were made by showing that targeting a protective antigen from Yersinia pestis to the IMV membrane of vaccinia virus led to enhanced and protective antibody responses in mice [78]. The benefits of membrane anchoring versus secretion may be antigen-dependent, as well as determined by the cell type infected, but such observations may warrant further investigation as new poxviral vectors are designed for optimal antibody induction.…”
Section: Mechanisms Of Antibody Induction By Poxviral Vectorssupporting
confidence: 56%
“…Intriguingly though, the study with recombinant vaccinia also assessed the merits of membrane-binding versus secretion of the encoded P. falciparum MSP1 antigen and reported the highest levels of functional antibody induction when the antigen was designed to anchor in the membrane. Similar observations were made by showing that targeting a protective antigen from Yersinia pestis to the IMV membrane of vaccinia virus led to enhanced and protective antibody responses in mice [78]. The benefits of membrane anchoring versus secretion may be antigen-dependent, as well as determined by the cell type infected, but such observations may warrant further investigation as new poxviral vectors are designed for optimal antibody induction.…”
Section: Mechanisms Of Antibody Induction By Poxviral Vectorssupporting
confidence: 56%
“…The lack of antibody response may be related to a defect in antigen presentation, e.g., the retention of the MVA expressed ASFV antigens inside infected cells may have limited their presentation to B-cells (Borrego et al, 2006;Ganges et al, 2005). The use of molecular elements such as tPA to enhance intracellularly expressed antigen secretion for B-cell recognition and MHC II presentation for priming of helper CD4 T-cells (Brewoo et al, 2010;Embry et al, 2011) has been previously reported. Since the administered MVA-ASFV constructs lacked the secretory tPA signal, the absence of observed antibody response may be due to limited B-cell presentation.…”
Section: Discussionmentioning
confidence: 98%
“…The secreted LcrV was a more potent vaccine that the previous vaccine that encoded the non-secreted form and the authors showed that a high level of protection was dependent on CD4 + but not CD8 + cells and correlated with increased anti-LcrV antibody and a bias toward IgG2a and away from IgG1 isotypes [194, 195]. In addition, Vaccinia virus (VACV) is the vaccine for smallpox and a widely-used vaccine vector for infectious diseases and cancers [196]. Several groups demonstrated that a vaccinia viral vector expressing either lcrV or caf1 (gene encoding F1) as vaccines which are highly immunogenic in BALB/c mice and safe in immunocompromised SCID mice [196198].…”
Section: Live Vectored Plague Vaccinesmentioning
confidence: 99%
“…In addition, Vaccinia virus (VACV) is the vaccine for smallpox and a widely-used vaccine vector for infectious diseases and cancers [196]. Several groups demonstrated that a vaccinia viral vector expressing either lcrV or caf1 (gene encoding F1) as vaccines which are highly immunogenic in BALB/c mice and safe in immunocompromised SCID mice [196198]. …”
Section: Live Vectored Plague Vaccinesmentioning
confidence: 99%